2015
DOI: 10.1039/c5dt02259b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterisation of bismuth(iii) hydroxamates and their activity against Helicobacter pylori

Abstract: Seven new bismuth(iii) hydroxamate complexes derived from the hydroxamic acids N-methylfurohydroxamic acid (H-MFHA), N-benzoyl-N-phenylhydroxamic acid (H-BPHA), salicylhydroxamic acid (H2-SHA), benzohydroxamic acid (H2-BHA), and acetohydroxamic acid (H2-AHA) have been synthesized and characterized. The complexes formed are either tris-hydroxamato complexes containing only mono-anionic ligands, [Bi(H-SHA)3], [Bi(MFHA)3] and [Bi(BPHA)3]; mixed-anion complexes, [Bi(SHA)(H-SHA)] and [Bi(AHA)(H-AHA)]; and potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…[41] However,m any bismuth complexes also exhibit good antibacterial activity, [40,[42][43][44][45] including bismuth carboxylates (used to treat Helicobacter pylori (H. pylori)i nfection), and certain "bismuth thiol" complexes which are known to inhibitb iofilm formation. [40,45] Our recent studies have shown that bismuth complexes of arene-sulfonates, amino-arene sulfonates and hydroxamates [46][47][48] act against H. pylori in low mm-high nm concentrations, which is orders of magnitudeb etter than current carboxylate based medications, while bismuth(III) thiolates derived from small heterocyclic thiones display remarkable broad-spectrum antibacterial activity (including against MRSA and VRE) at low mm concentrations. [49][50][51][52] Organophosphorus compounds, in particularp hosphinic acids (R 1 R 2 P(=O)OH), are known to have antibacterialp roperties.…”
Section: Introductionmentioning
confidence: 99%
“…[41] However,m any bismuth complexes also exhibit good antibacterial activity, [40,[42][43][44][45] including bismuth carboxylates (used to treat Helicobacter pylori (H. pylori)i nfection), and certain "bismuth thiol" complexes which are known to inhibitb iofilm formation. [40,45] Our recent studies have shown that bismuth complexes of arene-sulfonates, amino-arene sulfonates and hydroxamates [46][47][48] act against H. pylori in low mm-high nm concentrations, which is orders of magnitudeb etter than current carboxylate based medications, while bismuth(III) thiolates derived from small heterocyclic thiones display remarkable broad-spectrum antibacterial activity (including against MRSA and VRE) at low mm concentrations. [49][50][51][52] Organophosphorus compounds, in particularp hosphinic acids (R 1 R 2 P(=O)OH), are known to have antibacterialp roperties.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that benzohydroxamates were potentially more effective than the other complexes studied until now. Hence, further investigation of these complexes is required, and in same context novel bismuth (III) hydroxamates derived from N-methylfurohydroxamic acid (H-MFHA), N-benzoyl-Nphenylhydroxamic acid (H-BPHA), salicylhydroxamic acid (H2-SHA), and acetohydroxamic acid (H2-AHA) were also synthesized [102].…”
Section: Targeting Bismuthmentioning
confidence: 99%
“…The mechanisms for bacteria removal are unclear, although competition for ferric ions and interaction with regulatory proteins have been proposed (Li and Sun, 2012; Sun and Szeto, 2003). In addition, some novel Bi compounds such as hydroxamate benzohydroxamate derivatives have been synthesized, showing excellent antimicrobial activities (Pathak et al, 2014, 2015). The major drawback of Bi therapy is its toxicity when digested, but the development of new drugs through the combination of Bi with polysaccharides has shown greater activities with minimum adverse effects (Zhu et al, 2014).…”
Section: Application and Exposure Of Bimentioning
confidence: 99%